2010
DOI: 10.1101/gr.101410.109
|View full text |Cite
|
Sign up to set email alerts
|

The recombination landscape of the zebra finch Taeniopygia guttata genome

Abstract: Understanding the causes and consequences of variation in the rate of recombination is essential since this parameter is considered to affect levels of genetic variability, the efficacy of selection, and the design of association and linkage mapping studies. However, there is limited knowledge about the factors governing recombination rate variation. We genotyped 1920 single nucleotide polymorphisms in a multigeneration pedigree of more than 1000 zebra finches (Taeniopygia guttata) to develop a genetic linkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
328
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 227 publications
(367 citation statements)
references
References 83 publications
33
328
1
Order By: Relevance
“…To our knowledge, all analytical analyses and most of the simulations so far have assumed a uniform distribution of crossovers along chromosomes (see, for example, Franklin, 1977;Stam, 1980;Hill and Weir, 2011;Kardos et al, 2015;Wang, 2016; but see Suarez et al, 1979 andLibiger andSchork, 2007 for Monte Carlo simulations on relatedness). Although this assumption holds more or less for the human genome (Matise et al, 2007), linkage maps from other species have shown that the distribution of recombination along chromosomes can be highly biased toward the telomeres (Gore et al, 2009;Backström et al, 2010). We and others predicted that this results in a more block-like inheritance pattern of genomic segments on a given chromosome which in turn increases the Mendelian noise (Risch and Lange, 1979;Guo, 1995;Forstmeier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, all analytical analyses and most of the simulations so far have assumed a uniform distribution of crossovers along chromosomes (see, for example, Franklin, 1977;Stam, 1980;Hill and Weir, 2011;Kardos et al, 2015;Wang, 2016; but see Suarez et al, 1979 andLibiger andSchork, 2007 for Monte Carlo simulations on relatedness). Although this assumption holds more or less for the human genome (Matise et al, 2007), linkage maps from other species have shown that the distribution of recombination along chromosomes can be highly biased toward the telomeres (Gore et al, 2009;Backström et al, 2010). We and others predicted that this results in a more block-like inheritance pattern of genomic segments on a given chromosome which in turn increases the Mendelian noise (Risch and Lange, 1979;Guo, 1995;Forstmeier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been predicted that the distribution of crossovers along chromosomes will influence the amount of variance in IBD (see, for example, Risch and Lange, 1979;Rasmuson, 1993;Guo, 1995;Forstmeier et al, 2012), but to our knowledge it has never received attention in a modeling framework. Here we show that the variance in IBD is much larger in zebra finches than in humans, because in the former almost half of the genome is inherited in only six segments (that is, the interiors of chromosomes Tgu1, Tgu1A, Tgu2, Tgu3, Tgu4 and Tgu5) that only rarely break up by crossovers (Backström et al, 2010). Hill and Weir (2011) provide a formula to calculate the expected s.d.…”
Section: Mendelian Noise In Gwibdmentioning
confidence: 99%
See 3 more Smart Citations